Early Versus Late Recurrence of Hepatocellular Carcinoma After Surgical Resection Based on Post-Recurrence Survival: an International Multi-Institutional Analysis - Wei, T (2021)
Background: To define early versus late recurrence based on post-recurrence survival (PRS) among patients undergoing curative resection for hepatocellular carcinoma (HCC). Methods: Patients who underwent curative-intent resection for HCC between 2000 and 2017 were identified from an international multi-institutional database. The optimal cut-off time point to discriminate early versus late recurrence was determined relative to PRS. Results: Among 1004 patients, 443 (44.1%) patients experienced recurrence with a median recurrence-free survival time of 12 months. A cut-off time point of 8 months was defined as the optimal threshold based on sensitivity analyses relative to PRS for early (n = 165, 37.2%) versus late relapse (n = 278, 62.8%) (p = 0.008). Early recurrence was associated with worse PRS (median PRS, 27.0 vs. 43.0 months, p = 0.019), as well as overall survival (OS) (median OS, 32.0 versus 74.0 months, p < 0.001) versus late recurrence. In addition, patients who recurred early were more likely to recur at extra- ± intrahepatic (35.5% vs. 19.8%, p = 0.003) sites and were less likely to have the recurrence treated with curative intent (33.8% vs. 45.7%, p = 0.08). Patients undergoing curative re-treatment of late recurrence had a comparable OS with patients who had no recurrence (median OS, 139.0 vs. 140.0 months); patients with early recurrence had inferior OS after curative re-treatment versus patients with no recurrence (median OS, 69.0 vs. 140.0 months, p = 0.036), yet still better than patients who received palliative treatment for early recurrence (median OS, 69.0 vs. 21.0 months, p < 0.001). Conclusions: Eight months was identified as the cut-off value to differentiate early versus late recurrence. Curative-intent treatment for recurrent intrahepatic tumors was associated with reasonable long-term outcomes.